VIDEO BERTUTUR BAHASA MADURA DAN EMO DEMO SEBAGAI STRATEGI EFEKTIF EDUKASI KESEHATAN PENCEGAHAN STUNTING - Noviana, Ulva; Suryaningsih, Merlyna; Haris, Mustofa (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
Stunting is one of the cases of chronic malnutrition whose prevalence continues to increase from year to year in Indonesia. The results of a questionnaire completed by the Balita stunting family obtained data that 25 babies (83%) did not get colostrum milk because it was considered a primary milk, 11 babies aged 0-6 months (37%) received chopped rice / rice flour / fruit syrup / tajin / white water / honey water before the age of 6 months. It shows the behavior of a large family that cares about causing stunting on Balita. The method used in improving preventive behavior through health education with Emo Demo method and video media speaking Madura language. The participants were very enthusiastic about the delivery of material because they used interesting media such as video and Emo Demo about breastfeeding, mother-child bond, as well as demonstrations of breast-feeding MPI. The participants were able to explain the knowledge of stunting prevention and were capable of demonstrating the production of local and high-protein healthy. Keywords: stunting, Health education, Emo Demo, Video Education